Association analysis of single nucleotide polymorphisms in autophagy related 7 (ATG7) gene in patients with coronary artery disease. Issue 26 (30th June 2022) - Sarosh, Moomal; Nurulain, Syed Muhammad; Shah, Syed Tahir Abbas; Jadoon Khan, Muhammad; Muneer, Zahid; Bibi, Nazia; Shah, Syed Fawad Ali; Hussain, Sabir
Abstract : Recent experimental studies sparked the involvement of autophagy-related 7 (ATG7) in the development of atherosclerosis. However, the genetic variants and their association with coronary artery disease (CAD) are still to be unveiled. Therefore, we aimed to design a retrospective case-control study for the analysis of ATG7 gene polymorphisms and their association with CAD among the subjects originating from Pakistan. The ATG7 noncoding polymorphisms (rs1375206; Chr3:11297643 C/G and rs550744886; Chr3:11272004 C/G) were examined in 600 subjects, including 300 individuals diagnosed with CAD. Arginase-1 (ARG1) and nitric oxide metabolites were measured by the colorimetric enzymatic assay. Genotyping of noncoding ATG7 polymorphisms was accomplished by the polymerase chain reaction–restriction fragment length polymorphism method. A significant association of ATG7 (rs1375206 and rs550744886) was observed in individuals exhibiting CAD ( P < .0001, for each single-nucleotide polymorphism). Moreover, variant allele G at both loci showed high occurrence and significant association with the disease phenotype as compared to the wild-type allele (odds ratio [OR] = 2.03, P < .0001 and OR = 2.08, P < .001, respectively). Variant genotypes at ATG7 rs1375206 and rs550744886 showed significant association with high concentrations of ARG1 and low nitric oxide metabolites among the patients ( P < .0001 for each). A significant difference was noted in the distribution of the haplotype G-G, mapped at Chr3:11297643-11272004 between cases and controls ( P < .0001). The study concludes that ATG7 polymorphisms are among the risk factors for CAD in the subjects from Pakistan. The study thus highlights the novel risk factors for high incidents of the disease and reported for the first time to the best of our knowledge.